Karanga rua, karanga maha: Māori with lived experience of disability self-determining their own identities - Bernadette Jones; Paula Toko King; Gabrielle Baker; Linda Waimarie Nikora; Huhana Hickey; Meredith Perry; Rangi Pouwhare; Tristram Richard Ingham (Kōtuitui, 2024)
ABSTRACTFor Indigenous Māori in Aotearoa New Zealand, the impact of disability can be pervasive yet often invisible due to considerable gaps in the accuracy and interpretations of disability data and information for Māori. We present findings from a kaupapa Māori qualitative study that centres perspectives of Māori with lived experience of disability, exploring how they define and negotiate their identities within the context of health and wellbeing. Our findings emphasise how Western-centric constructs of ‘disability’ and related terms fail to align with te ao Māori perspectives. We discuss the notion of ‘karanga rua, karanga maha’ as a potential framework to understand how Māori with lived experience of disability conceptualise and express a plurality of identities within Māori collectives. Māori ways of being, knowing, relating and doing are vital to advancing understanding of the impacts of disability to address priorities and aspirations of Māori with lived experience of disability. There is a critical need for national level dialogue led by, with, and for Māori with lived experience of disability to define their collective identity, (re)claiming their own mātauranga and ways of knowing, in concert with recognition and acknowledgement of their tāngata whenua rights to full expression of tino rangatiratanga in their health and wellbeing.Glossary of Māori terms: aroha: love, compassion, empathy; hapū: kinship group, sub-tribe, sub-nation, to be pregnant; iwi: extended kinship group, tribe, nation, people, bone; ira: life principle; kaitiakitanga: guardianship; kanohi ki te kanohi: face-to-face; kapa haka: traditional Māori performing group; kāpō Māori: Māori with visual impairment, who are blind or deafblind; karanga: call or chant; karanga maha: person related through more than two lines of decent; karanga rua: someone related through two different lines, standing in a double relationship; ‘karanga rua, karanga maha’: a proposed framework for conceptualising Māori Disability identity - in reference to the integrated plurality of a person having two (rua) or many (maha) callings or intersectionally relational elements; kaumatua: elders; kaupapa Māori: Māori agenda, Māori principles, Māori ideology - a philosophical doctrine, incorporating the knowledge, skills, attitudes and values of Māori society; koro: elderly man, grandfather, term of address to an older man; kuia: elderly woman, grandmother, female elder; mana: spiritually sanctioned or endorsed influence, power and authority; manuhiri: visitor, guest; Māori: Indigenous Peoples of New Zealand; marae: courtyard, the open area in front of the wharenui, where formal greetings and discussions take place. Also used to include the complex of buildings; mātauranga: knowledge, wisdom; māuiui: illness, disorder; moemoeā: to have a dream, have a vision; ngāti Turi: Māori Deaf; Pākehā: foreign, New Zealander of European descent; Papatūānuku: Earth Mother; pēpi: baby, infant; rangatahi: younger generation; rangatira: chief/chieftainess; rohe: boundary, territory; rongoā: medicine, remedy; tamariki: children; tāngata: people; tāngata Turi: Māori Deaf; tāngata whaikaha: an empowering umbrella term used to encompass people (of all ethnicities) with lived experience of disability (literally: people striving for enablement); tāngata whaikaha Māori: an empowering umbrella term used to encompass Māori people with lived experience of disability (literally: people striving for enablement); tāngata whenua: people born of the land - of the placenta and of the land where the people's ancestors have lived and where their placenta are buried; tapu: sacred; te ao Māori: the Māori world; te ao Pākehā: the Pākehā (foreign) world; te ao tawhito: the ancient world; te reo Māori: the Māori language; Te Tiriti o Waitangi: the Māori version of the Treaty of Waitangi; forms the foundation of the contractual relationship between two internationally recognised sovereign nations – Māori, as tāngata whenua (people of the land), and the British Crown; tino rangatiratanga: absolute sovereignty, self-determination; tūrangawaewae: standing, place where one has the right to stand; tikanga Māori: customary system of values and practices developed over time and deeply embedded in the social context; tīpuna/tupuna: ancestors; wairua: spirit, soul; wānanga: to meet, discuss, deliberate, consider; Whaikaha: Te Reo Māori name of the Ministry of Disabled People; whakamā: to be ashamed, shy, bashful, embarrassed; whakapapa: ancestry, genealogy, familial relationships; whanau: to be born, extended family, family group; whānau hauā: a name for Māori with lived experience of disability; wharekai: dining hall; wharenui: meeting house, large house; whenua: placenta, ground, land.